SMARTPHONE ADDICTION AMONG UNDERGRADUATE GIRLS STUDENTS OF GOVERNMENT COLLEGES - Devi, Hijam Ranakumari; Meitei, Naorem Norjit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present study attempts to investigate on smartphone addiction among the girl students who are undergoing undergraduate course in government colleges of Thoubal district affiliated to Manipur University. The objective of the study is to study smartphone addiction of undergraduate girl students of government colleges with respect to subject stream and semester. In this study, the investigator has adopted descriptive method as method of the study. The investigator selected 265 undergraduate girl students of government colleges in Thoubal District as the sample of the study by using simple random sampling technique. For collection of the data, the investigator used Smartphone Addiction Scale developed by Dr. Vijayshri and Masaud Ansari. The main findings of the study is that there exists an average level of smartphone addiction among the undergraduate girl students of government colleges in Thoubal district.